GC-MS and Bioassay-Guided Isolation of Xanthones from Mammea siamensis - Wiyarat Kumutanat; Naowarat Kongkum; Napasawan Chumnanvej; Sakchai Hongthong; Sariyarach Thanasansurapong (Indonesian Journal of Chemistry, 2023)
Mammea siamensis (Miq.) T. Anders. (Calophyllaceae) plants have long been employed as an active integral composition in Thai traditional medicine. Additionally, phenylcoumarins and triterpenes were reported as major components in phytochemical research. This work explored the various parts of M. siamensis; barks, flowers, twigs, leaves, and young leaves; to determine their bioactive compounds. By using the GC-MS and bioassay guidance, two xanthones, 6-deoxyisojacareubin (1) and 1,5-dihydroxyxanthone (2), together with a mixture of phenylcoumarins, mammea A/AA cyclo D (3) and mammea A/AB cyclo D (4) have been isolated from the methanolic extract of young leaves. Their structures were identified by means of spectroscopic technique and by comparison with literature data. In particular, the current study was the first exposed report of xanthones 1 and 2 from the genus Mammea. Furthermore, compounds 1 and 2 and the methanolic young leaf extract had high antioxidant efficiency on DPPH and ABTS assays. The young leaf extract provided mild toxicity on the brine shrimp lethality test (BSLT) with LC50 value of 93.11 ± 1.37 µg/mL. In addition, the isolated compounds 1 and 2 were non-toxicity in BSLT assay. Therefore, the young leaf extract and the purified constituents 1 and 2 should be further studied and developed for using in pharmaceutical industries.